ANALYSIS OF THE HOSPITAL MANAGEMENT INFORMATION SYSTEM IN IMPROVING THE QUALITY OF HEALTH CARE SERVICES AND EMPLOYEE PERFORMANCE (SURVEY STUDY AT BHAYANGKARA HOSPITAL LEVEL III MANADO) - Litau, Natasya Anggreine; Yuliaty, Farida; Rasyid, Renaldi Prasetya Nagar; Kosasih, Kosasih; Rahmiyati, Ayu Laili (HEARTY, 2026)
Hospital management information system (HMIS) as one of the systems that plays a major role in the success of hospital documentation and services. This is because with the existence of an information technology system, it can help various organizational tasks run effectively and efficiently. The success of the implementation of HMIS should have a good impact on employee performance and service quality. This study aims to analyze the hospital management information system, health service quality and employee performance at Bhayangkara Hospital Level .III Manado. This study uses a quantitative approach. The sample in this study amounted to 78 respondents. Data analysis used is descriptive analysis and verification analysis using path analysis. The results of the descriptive analysis of the hospital management information system, health service quality and employee performance of respondents gave a good assessment, there were still some that needed to be improved. While the results of the verification study, the path analysis model showed that the path coefficient value between variables was positive and the indirect influence path coefficient value was greater than the direct influence (63.7%> 43.1%), meaning that the health service quality variable as an intervening variable was able to mediate the hospital information management system variable with employee performance variables.